Faktor yang Berhubungan dengan Perambahan Kawasan Hutan Lindung Gambut (Studi Kasus Desa Bram Itam Kanan Kecamatan Bram Itam Kabupaten Tanjung Jabung Barat) - Fazriyas, Fazriyas; Tamin, Rike Puspitasari; Irawan, Dede (Fakultas Kehutanan Universitas Jambi, 2018)
The purpose of this study is to identify factors that have a relationship with Peat Protected Forest encroachment Bram Itam River. This research was conducted in the village of Bram Bram Itam Itam Kanan District of West Tanjung Jabung Jambi Province. Data collection techniques used is a snowball sampling technique and obtained a sample of 30 farmers encroachers as respondents were then statistically analyzed the data using a dummy variable multiple linear regression. The results showed that the results of the regression analysis obtained a real relationship between the area of arable land in the protected forest area of peat with variable access to forests, legal sanctions and selling land. While the acreage with the permission of the village there is no real relationship. Factors that have a relationship with the encroachment of protected forest areas of peat River in the village of Bram is access to the forest is a factor, the factor of implementation of the sanctions law and land selling factor.